Analisis Dokumen Supervisi Akademik Islami terhadap Peningkatan Kinerja Guru di SMP Al-Hikmah Way Kanan - Antoro, Ardi; Arkhetafaza, Ulfa; Ifada, M Zakian (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
Teacher performance remains a critical issue in Islamic-based schools, particularly in ensuring instructional quality alongside the internalization of religious values. This study aims to conduct an in-depth analysis of Islamic-oriented academic supervision documents and explain their relationship to improving teacher performance at SMP Al-Hikmah Way Kanan, Lampung. The research employed a descriptive qualitative approach with a case study design. Data were collected through document analysis of supervision programs and instruments, limited observations of supervision implementation, and in-depth interviews with one principal and 4 supervised teachers. The findings indicate that Islamic academic supervision documents at SMP Al-Hikmah are systematically structured and integrated with Islamic values, encompassing supervision planning, classroom observation instruments, teacher performance evaluation formats, and follow-up action plans. The implementation of Islamic academic supervision is carried out through a humanistic participatory coaching pattern, in which the principal acts as both a moral-spiritual mentor and a technical supervisor. The study reveals that Islamic academic supervision positively influences teacher performance, as reflected in improved lesson planning, increased variation in teaching methods, strengthened professional attitudes, and the development of teachers’ awareness of teaching as a religious responsibility. Thus, Islamic academic supervision can be positioned as a strategic managerial instrument for improving teacher performance and learning quality in Islamic schools.